1999
DOI: 10.1021/ma981860r
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Photopolymerization of Epoxides by Direct and Sensitized Photolysis of Onium Tetrakis(pentafluorophenyl)borate Initiators

Abstract: Cationic photopolymerization of epoxides by the direct and sensitized photolysis of eight onium tetrakis(pentafluorophenyl)borates as initiators has been investigated. The relative reactivity of the onium borates on the photopolymerization was studied by the measurement of spectral sensitivity and by real time Fourier transform infrared spectroscopy. The kinetics of the photopolymerization by the sensitized photolysis was different from that of the direct photolysis. Several onium borates were sensitized by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…29, No. 4, 2016 The iodonium salt 1, known as Rhodorsil, works well as cationic initiator for photoinitiated curing of epoxies using UV radiation [12]. This salt has a high molecular weight (M = 1016 g•mol -1 ).…”
Section: S1mentioning
confidence: 99%
“…29, No. 4, 2016 The iodonium salt 1, known as Rhodorsil, works well as cationic initiator for photoinitiated curing of epoxies using UV radiation [12]. This salt has a high molecular weight (M = 1016 g•mol -1 ).…”
Section: S1mentioning
confidence: 99%
“…Anthracene was used as a sensitizer and can be sensitizing the onium borates. 7 IBVE was used as a monomer because its polymeriza- tion is well known. 14 -17 Irradiation was carried out using the light of a wavelength above 350 nm.…”
Section: Photopolymerization Of Ibve In Ch 2 CLmentioning
confidence: 99%
“…4 -7 In recent articles, we reported that some of the onium borates can be sensitized by anthracene and initiate photopolymerization of an epoxide. 6,7 However, polymerization rates of epoxy compounds are essentially lower than that of radical polymerizable compounds such as acrylates. On the other hand, vinyl ethers have relatively high reactivity in cationic polymerization and are not inhibited by atmospheric oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing interest in polymerizations initiated by external stimulation, such as photoirradiation or highenergy radiation, 1 and much effort has been devoted to develop systems that may initiate the polymerization processes through cationic 2,3,4 and radical mechanisms. 5,6 Cationic polymerization is widely applicable for both vinyl and ring-opening polymerizations giving place to many studies of both academic and industrial interests.…”
Section: Introductionmentioning
confidence: 99%